Characterization and design optimization of heterojunction photodiodes comprising n-type ultrananocrystalline diamond/hydrogenated amorphous carbon composite and p-type Si. (1st November 2018) - Shaban, Mahmoud; Zkria, Abdelrahman; Yoshitake, Tsuyoshi
Abstract: In this paper, we characterize and optimize design of a candidate ultraviolet photodiode based on nitrogen-doped ultrananocrystalline diamond hydrogenated amorphous carbon (UNCD/a-C:H) composite films grown on crystalline-Si substrates by coaxial arc plasma deposition. A comprehensive study including growth, fabrication, characterization, and modeling of the photodetector is presented here. The current-voltage characteristics of the device were reproduced and their critical parameters were extracted from a good matching between experimental and simulation results. A midgap acceptor-like defect state density of ~ 5 × 10 17 cm −3 eV −1 was found to be the dominant defect in the UNCD/a-C:H film, in addition to an interface defect density of ~ 3 × 10 13 cm −2 eV −1 at the interface of the UNCD/a-C:H film and the Si substrate. Experimental and simulation results showed that introducing an intrinsic UNCD/a-C:H layer in a pin heterostructure would significantly reduce the device leakage current and consequently improve its performance as an ultraviolet photodiode. Unoptimized fabricated devices exhibited a room temperature photoresponsivity of 135 mA/W measured under illumination of ultraviolet monochromatic light with a wavelength of 254 nm. The key parameters for optimized design of the device were extracted and investigated in details.